Answer:
x = -1/2 , 4
Step-by-step explanation:
1) If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.
2x+1=0
x−4=0
2) Set the first factor equal to 0.
2x+1=0
3) Subtract 1 from both sides of the equation.
2x=−1
4) Divide each term by 2 and simplify.
2x/2= −1/2
5) Cancel the common factor of 2.
x= −1/2
6) Move the negative in front of the fraction.
x = −1/2
7) Set the next factor equal to 0 and solve.
x=4
8) The final solution is all the values that make
(2x+1)(x−4) = 0 true.
9) x = −1/2 , 4